Leishmania (Leishmania) mexicana Infection in Wild Rodents from an Emergent Focus of Cutaneous Leishmaniasis in Yucatan, Mexico - Erika I. Sosa-Bibiano; Luis A. Sánchez -Martínez; Karina B. López-Ávila; Juan B. Chablé-Santos; Jimmy R. Torres-Castro; Edith A. Fernández-Figueroa; Claudia Rangel-Escareño; Elsy N. Loría-Cervera (Journal of Tropical Medicine)
In 2015, emergent cases of localized cutaneous leishmaniasis (LCL) were reported in Tinum, Yucatan, Mexico. As part of an eco-epidemiological study to characterize the elements that trigger Leishmania infection in that area, we conducted a field study to investigate the occurrence of Leishmania infection in wild rodents. From November 2019 to February 2020, rodents were caught from three sites located in the municipality of Tinum, Yucatan. For each specimen, clinical signs suggestive of Leishmania infection were recorded. Samples from the tail, liver, and spleen were taken for the identification of Leishmania DNA by PCR. Twenty rodents belonging to two species were caught including Heteromys gaumeri (55%, 11/20) and Ototylomys phyllotis (45%, 9/20). Fifty-five percent of the animals presented white spots on the tail, 15% had splenomegaly, and 5% had hepatomegaly. Fifty-five percent (11/20) of the animals were found infected by Leishmania. Heteromys gaumeri was caught in all trapping sites and was the most infected species (63.6%, 7/11). The percentage of infection for O. phyllotis was 44.4% (4/9). Leishmania (Leishmania) mexicana was identified as the infecting species in two H. gaumeri. This study provides, for the first time, evidence of Leishmania infection in wild rodents from the Yucatan state. Heteromys gaumeri and O. phyllotis may be involved in the transmission cycle of L. mexicana in this emergent focus; however, further longitudinal studies are needed to confirm their role as primary reservoirs.